A NARRATIVE INVESTIGATION ON TPACK ENGLISH TEACHERS’PROFICIENCIES - Cahyati, Sri Supiah; Rahmijati, Cynantia; Supartini, Nai (English Review: Journal of English Education, 2024)
Abstract: The introduction of the Merdeka curriculum has brought significant changes in the curriculum, particularly in terms of the autonomy and flexibility of teachers’ teaching especially regarding to digital literacy. The Merdeka curriculum is based on the Technological Pedagogical Content Knowledge (TPACK) framework, which seeks to integrate subject expertise, pedagogical skills, and technological content. Despite extensive research on TPACK, there is a noticeable gap in qualitative studies that explore teacher experiences and perceptions, particularly in the context of Indonesia’s Merdeka curriculum. The novelty of this research lies in its methodological approach—using Narrative Inquiry to explore the experiences of English teachers. This approach provides a deeper, more nuanced understanding of how teachers perceive and implement TPACK in their classrooms. To gain a comprehensive understanding of this issue, we examined 50 teachers from various regions in West Java. Our findings indicate that a significant portion of teachers (55%) have successfully incorporated technology in their teaching practices. Furthermore, the majority of teachers (84%) feel confident utilizing efficient teaching strategies and delivering targeted content (80%). We note that a large percentage of teachers (76%) exhibit proficiency in integrating technology into the teaching-learning process, while also acknowledging their proficiency in technology, pedagogy, and content (79%).However, we also identified several obstacles such as internet connectivity issues, which were identified as a significant potential hindrance (68%), students' unfamiliarity with the application (20%), and data quota limitations (5%) as restrictions. A minor yet distinguished percentage illuminated issues such as school procedures (3%), lack of access to smartphones (2%), and indecision in using LCD facilities (2%) as pitching factors that hinder the smooth merging of technology into teaching and learning. Based on the available evidence, it can be inferred that despite facing several obstacles, a majority of teachers have demonstrated a high level of confidence in their ability to implement digital literacy TPACK-related skills. These skills are essential for promoting effective teaching and learning in a digital age. However, it is important to note that the challenges faced by teachers in this regard cannot be ignored. To ensure that teachers are adequately equipped to navigate these challenges, it is essential to provide them with appropriate training and support. Moreover, the result of this study could contribute to the field of English language teaching, educational technology, and policymaking in education.